Harnessing Bacterial Signals for Suppression of Biofilm Formation in the Nosocomial Fungal Pathogen Aspergillus fumigatus - Reen, F. Jerry; Phelan, John P.; Woods, David F.; Shanahan, Rachel; Cano, Rafael; Clarke, Sarah; McGlacken, Gerard P.; O’Gara, Fergal (Frontiers in Microbiology, 2016)
Faced with the continued emergence of antibiotic resistance to all known classes of antibiotics, a paradigm shift in approaches towards antifungal therapeutics is required. Well characterised in a broad spectrum of bacterial and fungal pathogens, biofilms are a key factor in limiting the effectiveness of conventional antibiotics. Therefore, therapeutics such as small molecules that prevent or disrupt biofilm formation would render pathogens susceptible to clearance by existing drugs. This is the first report describing the effect of the Pseudomonas aeruginosa alkylhydroxyquinolone interkingdom signal molecules PQS and HHQ on biofilm formation in the important fungal pathogen Aspergillus fumigatus. Decoration of the anthranilate ring on the quinolone framework resulted in significant changes in the capacity of these chemical messages to suppress biofilm formation. Microscopic staining provided key insights into the structural impact of the parent and modified molecules, identifying lead compounds for further development.